THE ROLE OF READING IN BUILDING VOCABULARY AND LANGUAGE SKILLS - Usmonqulova Dinora Rahmatilla qizi; Saidqulova Elinura Quvondiq qizi; Khazratkulova Ezoza Ismat qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Introduction Reading is one of the best and most fun ways to increase vocabulary, strengthen language skills, and enhance communication. Frequent reading exposes readers to new words, phrases, and grammatical structures, allowing them to improve their comprehension of language, whether through fiction, non-fiction, or instructional materials. We will examine how reading affects vocabulary growth, improves language skills, and strengthens written and spoken communication abilities in this post.